Short-term effects of air pollution on childhood respiratory symptoms in general practice: a time-series analysis - Evelien R van Meel; A Burdorf; A Bohnen; P J E Bindels; Mata Sabine Fonderson; Saskia Willers; S van den Elshout (BMJ Paediatrics Open)
Objective To study the association between air pollutant concentrations and daily general practitioner (GP) consultations for respiratory problems in children in Rotterdam, Netherlands.Design A time-series study.Setting General practices in greater Rotterdam.Patients Children aged 0–17 years registered with participating GPs.Exposure Daily nitrogen dioxide (NO2), ozone (O3), particulate matter ≤2.5 µg/m3 (PM2.5) and particulate matter ≤10 µg/m3 (PM10) concentrations at GP addresses.Main outcomes measured Relative risk of respiratory consultations per 10 µg/m3 in pollutant concentration, adjusted for seasonality, pollen, day of the week and temperature.Results Over 100 000 consultations were analysed between 2015 and 2019. The baseline daily consultation rate was 18.12 per 1000 person-years. Children consulted their GP most frequently for acute upper respiratory infections (AURIs) (4.69 consultations per 1000 person-years), followed by asthma (3.68 consultations per 1000 person-years) and cough (2.31 consultations per 1000 person-years). Our results indicated that exposure to NO2 was predominantly associated with a decreased risk of GP consultations across most lag periods for all respiratory diseases (ARD), AURIs and asthma. In contrast, exposure to NO2 was generally associated with increased risk of GP consultations for cough. Conversely, exposure to O3 was associated with statistically significant increases in risk for ARD across all lag periods. Exposure to PM2.5 and PM10 showed opposite trends, with reduced risks in GP consultations for ARD and increased risks in consultations for AURI, asthma and cough.Conclusions Our findings expose a critical paradox on the impact of air pollution. For clinicians counselling families, these results emphasise that ‘good’ overall air quality days may still pose risks, although effects are small. High O3 increases total respiratory visits while particulate matter, though appearing protective overall, specifically exacerbates AURIs, asthma and cough. This divergence between total and specific respiratory effects indicates that comprehensive air quality policies must consider pollutant-specific impacts rather than assuming uniform effects.